2022
DOI: 10.3390/ijms23158281
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Metformin in the Brain: A New Perspective of Metformin Treatments in Related Neurological Disorders

Abstract: Metformin is a first-line drug for treating type 2 diabetes mellitus (T2DM) and one of the most commonly prescribed drugs in the world. Besides its hypoglycemic effects, metformin also can improve cognitive or mood functions in some T2DM patients; moreover, it has been reported that metformin exerts beneficial effects on many neurological disorders, including major depressive disorder (MDD), Alzheimer’s disease (AD) and Fragile X syndrome (FXS); however, the mechanism underlying metformin in the brain is not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 199 publications
0
20
0
1
Order By: Relevance
“…This is supported by a growing body of in vitro and in vivo studies of PD. [65][66][67] First, known as a strong AMPK (5'-adenosine 20 mono-phosphate-activated protein kinase) activator, metformin's neuroprotective effects may be primarily attributable to its role in activating the AMPK signaling pathway. 68,69 Past research found that AMPK can suppress microglial activation, thus potentially mitigating neuroinflammation.…”
Section: And Table 2)mentioning
confidence: 99%
“…This is supported by a growing body of in vitro and in vivo studies of PD. [65][66][67] First, known as a strong AMPK (5'-adenosine 20 mono-phosphate-activated protein kinase) activator, metformin's neuroprotective effects may be primarily attributable to its role in activating the AMPK signaling pathway. 68,69 Past research found that AMPK can suppress microglial activation, thus potentially mitigating neuroinflammation.…”
Section: And Table 2)mentioning
confidence: 99%
“…An experimental study observed that metformin improves GABAergic neurotransmission in diabetic rats by regulating brain metabolism and insulin signalling in diabetic rats 155 . Recent studies suggest that metformin appears not only to regulate synaptic transmission or plasticity in pathological conditions including epilepsy but also to regulate the balance of excitation and inhibition balance in neural networks 156 . Metformin can promote the membrane insertion of GABA A receptor and enhance the inhibitory synaptic neurotransmitter function and micro‐inhibitory postsynaptic currents in cultured rat hippocampal neurons by activating AMPK‐FOXO3A signalling pathway and increasing the expression of GABA A receptor‐associated protein 157 .…”
Section: The Mechanistic Role Of Metformin In Epilepsymentioning
confidence: 99%
“…Besides, many studies have shown that diabetes drugs (such as metformin, sulfonylureas, and pioglitazone etc.) not only play a role in blood glycemic control, but also can impact on neuroprotection, neurogenesis, neuroinflammation, synaptic plasticity, and proteins aggregationthrough different mechanisms and linking pathways, in order to reduce the risk of suffering from AD [39][40][41][42][43][44]. Moreover, early and effective control of hyperglycemia has a positive impact on reducing the risk of AD and delaying the progress of AD, and neurodegeneration plays an important role in this process.…”
Section: Admentioning
confidence: 99%